Carbothermal synthesis of micro-scale spherical AlN granules with CaF2 additive - Wang, Qi
In this work, we purposefully reported a simple yet efficient carbothermal synthesis strategy to prepare micro-scale spherical AlN granules just by using CaF2 as promoting additive. The effects of synthesis parameters, such as CaF2 content, N-2 gas pressure, reaction temperature, upon the nitridation rate, surface morphology and particle size were comprehensively investigated. It was established that elevated N-2 gas pressure, high reaction temperature and abundant Ca-aluminates liquid synergistically promoted the formation of micro-scale spherical AlN granules. Additionally, the reduction and nitridation of intermediate Ca-aluminates played a significant role in improving the nitridation rate, increasing the particle size and forming the smooth spherical appearance. More significantly, the underlying reaction mechanism in the carbothermal synthesis of spherical AlN with CaF2 additive was also tentatively proposed. (C) 2015 Elsevier B.V. All rights reserved.